2011
DOI: 10.1111/j.1365-2702.2010.03534.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of patient education and home monitoring on medication compliance, hypertension management, healthy lifestyle behaviours and BMI in a primary health care setting

Abstract: Patient education medication adherence alone and in combination with healthy lifestyle behaviour teaching is an effective tool for blood pressure reduction in the hypertensive population in primary health care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
0
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(142 citation statements)
references
References 29 publications
4
124
0
14
Order By: Relevance
“…These patients are inconsistent with taking medicines, they can forget, they stop taking them of their own accord, and they only take them when they feel unwell [13,26]. Studies have shown that these behaviors are closely related to inadequate monitoring of and explanation about the use of medications, lack of explanation at the onset of the drug treatment, not believing in the efficacy of the medication, high costs of medicines, failure or neglect to renew the prescription when the medicine finishes [14]. Therefore, if patients are informed about medication use and their awareness of medication use is raised when they are diagnosed with hypertension or followed in health centers, the problem of inappropriate medication use will be solved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These patients are inconsistent with taking medicines, they can forget, they stop taking them of their own accord, and they only take them when they feel unwell [13,26]. Studies have shown that these behaviors are closely related to inadequate monitoring of and explanation about the use of medications, lack of explanation at the onset of the drug treatment, not believing in the efficacy of the medication, high costs of medicines, failure or neglect to renew the prescription when the medicine finishes [14]. Therefore, if patients are informed about medication use and their awareness of medication use is raised when they are diagnosed with hypertension or followed in health centers, the problem of inappropriate medication use will be solved.…”
Section: Discussionmentioning
confidence: 99%
“…• Individual Interview Form: This form was created by the researchers in accordance with the literature [6,13,14]. It consisted of 27 closed-and open-ended questions aimed at determining individuals' sociodemographic characteristics, their lifestyle behaviors, their reasons for admission to the emergency department and their chronic illnesses.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For those who are taking antihypertensive medications, good medication adherence is important to ensure optimal control of hypertension (4). Therefore, promoting medication adherence in patients with poor control of their BP is an important role for nurses and healthcare providers (5). A major contributor to poor BP control may be patient non-adherence to prescribed antihypertensive medication (6).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension (HTN) is the third leading cause of death worldwide, causing 7.5 million deaths annually (12.8% of all deaths) (1,2). The prevalence of HTN globally in 2014 in men aged 18+ years was 24% and in women was 20.5%.…”
Section: Introductionmentioning
confidence: 99%